Work experience, profession type, and perception of medication waste disposal among healthcare workers: A study in the Eastern Province, Saudi Arabia - Fatimah A. Alqassab; Ahrar Alhujiri; Ghadeer Alsheef; Ahmed Almosabeh; Manal Surour; Aymen Alqurain (Elsevier, 2024)
Background: Improper disposal of medication waste is a global concern. Several published articles reported perceptions and barriers of the community or pharmacists towards proper medications waste disposal, but least are discussing the overall health workers' perception, particularly those in the Eastern Province in Saudi Arabia. Aim and objectives: The current research aimed to identify the healthcare worker's perception, explore limitations and barriers, and proposed solutions towards proper medication waste disposal. The second aim is to investigate difference in the response among healthcare worker based on their profession type and years of work experience. Method: This cross-sectional, descriptive study is based on an internet-based survey questionnaire. Questionnaires were adapted from previous study and were validated before distribution to participants. Respondents were classified based on their healthcare profession and based on the year of their work experience. Descriptive statistics analysis was carried out to assess difference in perception among respondents based on their profession or years of work experience. The Statistical Package for the Social Sciences (SPSS, version 26) package was used for conducting statistical analysis. Results: 321 participants responded to the online survey. 60 % of the respondents were from clinical practice settings and 26 % had work experience between 0-2 years. 77 % of them had encountered medication waste issues, whereas 129 respondents reported that these issues raised from the workplace and 92 respondents reported that they raised personal source. Interestingly, respondents with limited work experience reported the lower perception and knowledge toward mediation waste compared to those with more work experience. 31 % agreed that logistic issues (availability of collection bins) and 28 % reported that the unavailable policies/guidelines that govern this proper medication waste disposal are barriers which limit proper practice. 211 participants strongly agreed on that policies from governmental bodies are very important to limit this issue, whereas training and the availability of logistics were the most recommended solutions from respondents to increase healthcare awareness towards proper medication waste disposal. Conclusion: Proper perception about medication waste disposal is still an ongoing issue among healthcare workers, particularly those who recently joined their work. Training and enforcing policies and guidelines by governmental bodies could be one approach to ensure proper medication waste disposal.